Appunti per una ricerca sui riti di carnevale lungo il confine friulano-sloveno: l'eredita di Niko Kuret - Dapit, Roberto (Traditiones (Ljubljana), 2001)
In his article titled "Ceremonial Masks along the Border between Slovenia and Friul-Venezia Giulia" the author analyzes some basic questions (the theory of manism, ceremonial processions, the people behind the mask, etc.) which had been examined by Niko Kuret, a prominent results obtained by researchers in Italy and Friuli-Venezia Giulia. He expects that Kuret's research results will present the basis and provide the necessary initiative for further research of ceremonial masks along the border between Slovenia and Friuli-Venezia Giulis
Keywords: ethnology; etnologija; maske; Slovenia; Slovenija; Friuli–Venezia Giulia; Furlanija-Julijska krajina